Placental Sampling for Understanding Viral Infections — A Simplified Protocol for the COVID-19 Pandemic - Nobrega, Guilherme de Moraes; Guida, José Paulo Siqueira; Japecanga, Rodolfo Rosa; Antolini-Tavares, Arthur; Mysorekar, Indira; Costa, Maria Laura (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The coronavirus disease 2019 (COVID-19) is a pandemic viral disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The impact of the disease among the obstetric population remains unclear, and the study of the placenta can provide valuable information. Adequate sampling of the placental tissue can help characterize the pathways of viral infections.Methods A protocol of placental sampling is proposed, aiming at guaranteeing representativity of the placenta and describing the adequate conservation of samples and their integrity for future analysis. The protocol is presented in its complete and simplified versions, allowing its implementation in different complexity settings.Results Sampling with the minimum possible interval from childbirth is the key for adequate sampling and storage. This protocol has already been implemented during the Zika virus outbreak.Conclusion A protocol for adequate sampling and storage of placental tissue is fundamental for adequate evaluation of viral infections on the placenta. During the COVID-19 pandemic, implementation of this protocol may help to elucidate critical aspects of the SARS-CoV-2 infection.
Keywords: COVID-19; placenta; pregnancy; systematic sampling; viral infections